Integration of Diagnostics in High Power Laser Systems for Optimization of Laser Material Processing - Biermann, S; Hutfless, J; Geiger, Manfred (SPIE- High Power Lasers. Int. Conf. OE/Laser 91, 1991)
Experimental investigations on high power CO2-laser systems has been carried out. To ensure the processing quality and to allow a fast reaction in case of an accident a diagnostic system was developed and realized with integrating special equipment for on-line and off-line diagnostics for laser beam, gasflow and workpiece temperature.
LFT Import::2019-08-05 (229)